Management Practices, Disease Incidence, Uses of Indigenous Knowledge, and Conditions and Problems of the Poultry Farmers in Rajshahi, Bangladesh - Dutta, Ripon Kumar; Islam, M Saiful; Kabir, Md Ashraful (Journal of Life and Earth Science, 2014)
Data on management practices, incidences of common diseases, uses of indigenous knowledge (IK) and conditions and problems of the poultry farmers in some selected areas of Rajshahi, Bangladesh, were investigated. Data from small, medium and large poultry enterprises situated in the urban, semi-urban and rural areas at six Upozillas of Rajshahi District viz., Boalia, Godagari, Motihar, Mohonpur, Poba and Rajpara were collected. An indigenous (IND), four exotic (EXO) viz. Cob 500 breed of broiler, Cockerel, Fayoumi (FAY), and Rhode Island Red (RIR), and a crossbred (CRO) called Sonali (derived from RIR cock × FAY hen) chicken breeds were included in the study. Eighteen parameters on management practices, 13 diseases, 20 indigenous knowledge (IK) items, 3 major conditions, 11 problems encountered and top 10 opinions of the poultry farmers were identified. Satisfactory to good management practices were recorded for IND in Godagari and that for EXO and CRO in Rajpara. All the remaining farms practiced moderate to unacceptable management practices. Bacillary white diarrhoea (39.56%), omphalitis (57.40%) and hypervitaminosis (55.56%) were the most frequent diseases whereas common cold (10.16%), bacillary white diarrhoea (32.82%) and bacillary white diarrhoea (27.62%) were the least frequent diseases for IND, EXO and CRO chickens, respectively. However, no incidence of bird flu (avian influenza) was recorded during the survey period. Uses of broody hens (82.25%), changing of waterier (62.45) and vaccination (49.19) were found to be the prevalent IK items for IND, EXO and CRO birds. Separating healthy versus diseased respectively, chicks (26.45%), feeding maize grain (52.45%) and feeding molasses (49.10%) were healthcare IK items for the chicken breeds, respectively. Majority of the poultry farmers of IND, EXO and CRO breeds had respectively primary (50.08%), graduate (47.18%) and higher secondary (45.77%) education levels. Agriculture (60.71%), miscellaneous (46.14%) and miscellaneous (35.50%) were dominant occupations among the three categories of poultry farmers. IND farmers predominantly had cultivable land (50.16%) in comparison with the cultivable landholdings by the EXO (21.69%) and homestead landholdings by their CRO (31.16%) counterparts. Poor housing (44.86%), disorganized and unreliable marketing system (52.05%) and lack of institutional credit facilities (47.89%) were identified to be the major problems for the IND, EXO and CRO farmers respectively, who opined strongly in favour of improved native breeds (30.04%), proper breeding facilities (49.90%) and government co-operation (48.01%). The impacts of these findings on the poultry enterprise in Rajshahi have been discussed. DOI: http://dx.doi.org/10.3329/jles.v7i0.20120 J. Life Earth Sci., Vol. 7: 43-49, 2012